Implementation of the Unified Modeling Language (UML) Method in the Development of Employee Payroll Information Systems - M. Himam Zulfana; Nur Hadian (Smart Comp :Jurnalnya Orang Pintar Komputer, 2026)
The development of an employee payroll information system is important in improving the efficiency and accuracy of payroll data management, especially in companies with a large number of employees. The selection of this topic is driven by the need to reduce payroll errors that often occur in manual systems. The Unified Modeling Language (UML) method was chosen as the main approach because of its ability to model and visualize the system in a structured manner. This research uses an object-oriented approach with UML, which includes the creation of use case diagrams, class diagrams, activity diagrams, and sequence diagrams. These diagrams are used to describe the functional requirements and business processes that support the development of payroll information systems. The results show that the application of UML helps simplify system design, facilitate communication between developers and stakeholders, and increase accuracy in system implementation. Based on the results of the tests that have been carried out, the successful performance of the information system runs effectively and accurately. In conclusion, this method is effective in designing an efficient and reliable payroll information system to minimize errors and increase productivity.